Role of Induced Mutations for Enhancing Nutrition Quality and Production of Food - Chakraborty, Nihar Ranjan; Paul, Amitava (International Journal of Bio-resource and Stress Management, 2023)
Crop plants form the major components of human diets, providing the required calories and nutrients to sustain life. World is facing a food and energy crisis of unprecedented proportions. Food production, to meet the needs of the growing world population, can be augmented by improving agronomic techniques and by growing genetically improved cultivars of a wide range of crops. Induced mutations are a proven tool in creating a wealth of desirable genetic variability in plants and can be a catalyst in developing improved crop varieties with nutrition quality, and higher yield. The commercial utilization of approximately 3,000 mutants strongly shows that mutation breeding is a useful tool for generating new germplasm for crop improvement. Induced mutations will continue to have an increasing role in creating crop varieties with traits such as modified oil, protein and starch quality, to the enhancement of phytonutrients in fruits and reduction of anti-nutrients in staple foods.